2023
DOI: 10.1515/oncologie-2023-0090
|View full text |Cite
|
Sign up to set email alerts
|

Screening and biomarker assessment of ferroptosis genes FLT3 and ALOX5 in lung adenocarcinoma

Abstract: Objectives Ferroptosis is a unique process of cell death that specifically requires iron. We investigated ferroptosis genes and their function in lung adenocarcinoma (LUAD) patients. Methods Data on the expression levels of genes associated with ferroptosis were collected from the FerrDb and the Cancer Genome Atlas database. Kaplan-Meier Plotter was employed to generate the survival curves of LUAD patients with high vs low ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Moreover, TMB defined by the number of somatic mutations, including synonymous and intron mutations, per 38 Mb of genome area for targeted sequencing, has shown that higher TMB correlates with improved survival in bladder cancer patients receiving immune checkpoint inhibitor treatments [77][78][79][80]. LUAD, representing almost 40% of lung cancer cases, is a prevalent subtype and is noted for its high morbidity and mortality rates globally [37,81]. In China, lung cancer has been the most rapidly increasing malignancy over the past 30 years, predominantly comprising histological subtypes such as adenocarcinoma and squamous cell carcinoma, which make up 80%-85% of cases, with the remainder being small cell lung cancer (atezolizumab plus etoposide/platinum) [58,82].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TMB defined by the number of somatic mutations, including synonymous and intron mutations, per 38 Mb of genome area for targeted sequencing, has shown that higher TMB correlates with improved survival in bladder cancer patients receiving immune checkpoint inhibitor treatments [77][78][79][80]. LUAD, representing almost 40% of lung cancer cases, is a prevalent subtype and is noted for its high morbidity and mortality rates globally [37,81]. In China, lung cancer has been the most rapidly increasing malignancy over the past 30 years, predominantly comprising histological subtypes such as adenocarcinoma and squamous cell carcinoma, which make up 80%-85% of cases, with the remainder being small cell lung cancer (atezolizumab plus etoposide/platinum) [58,82].…”
Section: Discussionmentioning
confidence: 99%
“…LUAD is represented by highly inflammatory infiltration ( Luo et al, 2020 ; Zheng et al, 2023 ). The early asymptomatic characteristics of LUAD often leads to a late diagnosis of most LUAD patients as well as a poor cancer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of LUAD is not ideal, and the 5‐year survival rate of most patients usually remains below 15% 5 . At present, due to the progress of diagnosis and lifestyle changes, the incidence of LUAD has increased slightly, and more than 70% of patients have been diagnosed when they have advanced to the middle and late stages 6,7 . Radiation therapy is a useful and commonly used therapeutic tool for lung cancer patients, and it plays a key role in achieving local tumour control while limiting damage to surrounding tissues 8 .…”
Section: Introductionmentioning
confidence: 99%
“…have been diagnosed when they have advanced to the middle and late stages. 6,7 Radiation therapy is a useful and commonly used therapeutic tool for lung cancer patients, and it plays a key role in achieving local tumour control while limiting damage to surrounding tissues. 8 Although only a portion of individuals experience positive results from radiation treatment, deciphering the molecular factors that influence how individuals respond to cancer therapy remains a significant obstacle in the field of oncology.…”
mentioning
confidence: 99%